Three-Dimensional Image Fusion of SPECT and CT Scans for Locating Sentinel Lymph Nodes in Malignant Melanomas - Akiyama, Michiko (S. Karger AG, 2011)
Image fusion software can derive a fusion image from single photon emission computed tomography and computed tomography scans. We applied a three-dimensional fusion image to detect sentinel lymph nodes (SLNs) in 3 patients with malignant melanomas of the lumbar, vulvar and head region, respectively. During each operation, we detected SLNs at the expected site, as indicated by the fusion images. The three-dimensional image fusion could thus be confirmed as a simple and helpful method for precisely localizing SLNs in these patients.